Raman scattering in sulphide glasses - Tolmachov, I.D.; Stronski, A.V.; Pribylova, H.; Vlček, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Raman spectra of two ternary glasses of composition Ge₅As₃₇S₅₈ and As₄Ge₃₀S₆₆ have been investigated. An influence of addition of third element on the spectra of binary glasses has been studied by comparison with spectra of two binary glasses of composition Ge₃₃S₆₇ and As₄₀S₆₀. Glass structure and phase separation effects are discussed.